(untitled) (Práxis Educativa, 2018)
Several universities offer teaching continuous development courses and support to new professors with the purpose of leading them to concentrate more on their students’ learning than on transmitting knowledge. However, have such continuous development and follow-up had any effect on the teaching strategies employed by those professors? Is there a distinction between these strategies and those used by professors who are not in continuous development projects? This text presents data collected along three years, through observation and interviews, with 22 new professors, from which 9 are in continuous development courses, 8 have completed such courses and are in a follow-up phase and 5 who have never taken part in continuous development courses. The results have not revealed noticeable difference between these professors, which leads to the conclusion that all of the them employed strategies that go beyond knowledge transmission. Keywords: Continuous development. Education follow-up. New Professors. Teaching Strategies. University.